Attitudes and policies toward Turgut Ozal issue Kurdish 1984-1993 (Journal of the College of Education for Women, 2019)
After receipt of military commanders power in 1980, they were determined to solve theKurdish question by force, just like their predecessors in resolving such issues, and thesituation became worse when the Kurdish resistance in a more organized than previous yearsand behind the Party (PKK) .After the mass support of the Kurdish widespread party get involved most of the Kurdishyouth in the party organization of the (PKK), prompting Turkish President then to makedecisions and take immediate action firm against the party, but the Kurdish issue beganTthlhal when he arrived at the helm of President Turgut Ozal in 1989, he worked on thedevelopment of the areas inhabited by the Kurds, specifically the Southeast Anatolia and theevents of demographic changes And reduce the cultural differences between the eastern andsouthern sections eastern and western sections of the country through the employmentpossibilities and capabilities enjoyed by the province of the same natural resources and riverbasins, and the hands of the worker, then the followers of the new policy is more flexible andopenness towards the Kurds.